Humerus Compression Plate Analysis Using ANSYS Software - HAIDIR, KHAIRUN NISA MAHFUZAH; ISMAIL, AL EMRAN (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A compression plate is a type of orthopaedic implant used to fix bone fractures. It is a metal plate that is screwed onto the surface of the bone to hold the broken pieces together and promote healing. They are available in different shapes and sizes to fit the specific bone and fracture pattern. Certain aspects of the humerus, such as overall length and the angles of curvature, can vary among individuals. Additionally, the size and prominence of muscle attachment sites on the bone can differ based on factors like genetics, age, and lifestyle. The study addresses the absence of research on the load applied to the design of humerus compression plates at 0 degrees and 30 degrees. Existing Finite Element (FE) studies on proximal humeral plates have predominantly focused on aspects such as screw configuration, bone cement augmentation, and optimization of implant design and properties. This study employs ANSYS software to conduct a thorough analysis of humerus compression plates with 30-degree and 0-degree configurations, focusing on equivalent von Mises stress and displacement under various loading conditions. Results indicate that the 0-degree abduction load yields significantly lower equivalent von Mises stress compared to adduction, extension, flexion, and axial compression, suggesting superior biomechanical performance. Additionally, the investigation reveals that the 30-degree compression plate exhibits the most favourable displacement characteristics during axial compression, emphasizing its potential as the preferred design for enhanced stability in clinical applications. These findings contribute valuable insights to the optimization of humerus compression plate design, guiding advancements in orthopaedic implant technology and ultimately improving patient outcomes.